Genomic and transcriptional analysis of genes containing fibrinogen and IgSF domains in the schistosome vector Biomphalaria glabrata, with emphasis on the differential responses of snails susceptible or resistant to Schistosoma mansoni. - Lijun Lu; Eric S Loker; Coen M Adema; Si-Ming Zhang; Lijing Bu (Public Library of Science (PLoS), 2020)
Achieving a deeper understanding of the factors controlling the defense responses of invertebrate vectors to the human-infecting pathogens they transmit will provide needed new leads to pursue for control. Consequently, we provide new genomic and transcriptomic insights regarding FReDs (containing a fibrinogen domain) and FREPs (fibrinogen domain and one or two IgSF domains) from the planorbid snail Biomphalaria glabrata, a Neotropical vector of Schistosoma mansoni, causative agent of human intestinal schistosomiasis. Using new bioinformatics approaches to improve annotation applied to both genome and RNA-Seq data, we identify 73 FReD genes, 39 of which are FREPs. We provide details of domain structure and consider relationships and homologies of B. glabrata FBG and IgSF domains. We note that schistosome-resistant (BS-90) snails mount complex FREP responses following exposure to S. mansoni infection whereas schistosome-susceptible (M line) snails do not. We also identify several coding differences between BS-90 and M line snails in three FREPs (2, 3.1 and 3.2) repeatedly implicated in other studies of anti-schistosome responses. In combination with other results, our study provides a strong impetus to pursue particular FREPs (2, 3.1, 3.2 and 4) as candidate resistance factors to be considered more broadly with respect to schistosome control efforts, including involving other Biomphalaria species vectoring S. mansoni in endemic areas in Africa.